ANALISIS KINERJA KEUANGAN PADA KOPERASI TIRMA MART (WASERDA) PERUSAHAAN DAERAH AIR MINUM KABUPATEN KUTAI KARTANEGARA - Julianti, Ellisa Julianti (EKONOMIA, 2019)
Generally, the performance of the Tirma Mart Cooperative (Waserda) is only evaluated based on financial statements without using financial ratios to know for certain whether there is an improvement in the efficiency level or not. The aim of this research is to find out whether financial performance with solvency and profitability liquidity ratios in Tirma Mart (Waserda) Cooperative Regional Water Supply Company in Kutai Kartanegarat Regency in 2017 is better than in 2016 and 2015. The analytical tool used in this study is a financial ratio analysis tool as a basis for measuring financial performance. Measurement of financial performance is known from the ratio of liquidity, solvency and profitability. Based on the results of the discussion of financial performance analysis, it can be concluded that the overall hypothesis about the financial performance of the proposed company is rejected or not proven true. In the hypothesis proposed that the financial performance of the Tirma Mart Cooperative Company (Waserda) has increased and decreased from the previous year, both in terms of increased liquidity, solvency ratios that have experienced an increase and decrease and a profitability ratio that has decreasedÂ